Use of a new-generation reverse tetracycline transactivator system for quantitative control of conditional gene expression in the murine lung - Dürr, Julia; Gruner, Maren; Schubert, Susanne C.; Haberkorn, Uwe; Bujard, Hermann; Mall, Marcus A. (American journal of respiratory cell and molecular biology, 2011)
Conditional regulation of gene expression by the combined use of a lung-specific promoter and the tetracycline-regulated system provides a powerful tool for studying gene function in lung biology and disease pathogenesis in a development-independent fashion. However, the original version of the reverse tetracycline-dependent transactivator (rtTA) exhibited limited doxycycline sensitivity and residual affinity to its promoter (Ptet), producing leaky transgene expression in the absence of doxycycline. These limitations impeded the use of this system in studying gene dosage effects in pulmonary pathogenesis and repair mechanisms in the diseased lung. Therefore, we used a new-generation rtTA, rtTA2s-M2, with no basal activity and increased doxycycline sensitivity, and the rat Clara cell secretory protein (CCSP) promoter to target its expression to pulmonary epithelia in mice. Novel CCSP-rtTA2s-M2 founder lines were crossed, with bi-transgenic reporter mice expressing luciferase and Cre recombinase. Background activity, doxycycline sensitivity, tissue and cell-type specificity, inducibility, and reversibility of doxycycline-dependent gene expression were determined by luciferase activity, immunohistochemistry, morphometry, and bioluminescence measurements in neonatal and adult lungs. We generated two distinct novel CCSP-rtTA2s-M2 activator mouse lines that confer tight and doxycycline dose-dependent regulation of transgene expression, with high inducibility, complete reversibility, and no background activity, in airway and alveolar epithelia. We conclude that rtTA2s-M2 enables quantitative control of conditional gene expression in respiratory epithelia of the murine lung, and that the new CCSP-rtTA2s-M2 activator mouse lines will be useful in the further elucidation of the pathogenesis of complex lung diseases and in studies of lung repair.